2003
DOI: 10.1002/path.1421
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Fourier transform infrared microspectroscopy in studies of benign prostate and prostate cancer. A pilot study

Abstract: Fourier transform infrared (FTIR) microspectroscopy has been applied to a study of prostate cancer cell lines derived from different metastatic sites and to tissue from benign prostate and Gleason-graded malignant prostate tissue. Paraffin-embedded tissue samples were analysed by FTIR, after mounting onto a BaF(2) plate and subsequent removal of wax using Citroclear followed by acetone. Cell lines were analysed as aliquots of cell suspension held between two BaF(2) plates. It was found that the ratio of peak a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
106
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(121 citation statements)
references
References 25 publications
8
106
0
2
Order By: Relevance
“…These results also agree with the increase in the intensity of the shoulder around 1170 cm À1 in the imatinib resistant cancer cells indicating protein phosphorylation [46]. Gazi et al suggested that the intensity ratio of the 1030 cm À1 and 1086 cm À1 bands could be interpreted as glycogen-to-phosphate ratio and proposed as a marker for cancer to distinguish benign and malignant prostate cancer and they concluded that the ratio decreased in malignant tissue [47].…”
Section: Discussionsupporting
confidence: 79%
“…These results also agree with the increase in the intensity of the shoulder around 1170 cm À1 in the imatinib resistant cancer cells indicating protein phosphorylation [46]. Gazi et al suggested that the intensity ratio of the 1030 cm À1 and 1086 cm À1 bands could be interpreted as glycogen-to-phosphate ratio and proposed as a marker for cancer to distinguish benign and malignant prostate cancer and they concluded that the ratio decreased in malignant tissue [47].…”
Section: Discussionsupporting
confidence: 79%
“…The phosphate level was higher for normal cells carbohydrate levels also showed a corresponding increase than for H-ras transfected malignant cells (Ramesh et al, 2001). In a study by Gazi et al the intensity ratio of the 1030 cm À1 and 1086 cm À1 bands was interpreted as glycogen-to-phosphate ratio and proposed as a marker for cancer to distinguish benign and malignant prostate cancer and they concluded that the ratio decreased in human malignant tissue (Gazi et al, 2003). Their findings indicate a close connection between carbohydrate and lipid metabolisms in the development of malignant cancer cells and the subject should be investigated metabolically.…”
mentioning
confidence: 99%
“…These include benign and malignant prostate (Gazi et al, 2003(Gazi et al, , 2004(Gazi et al, , 2006, colon (Lasch et al, 2002) and cervical tissues, all of which have been evaluated using this technique and with a high rate of diagnostic accuracy. In relation to grading of CaP, the sensitivities and specificities reported earlier have been as high as 78 and 89%, respectively, using a Fourier transform infrared-linear discriminant analysis model to predict Gleason scores less than 7 (GSo7), equal to 7 (GS ¼ 7) and greater than 7 (GS47) (Gazi et al, 2006).…”
mentioning
confidence: 99%
“…Prostate cancer (CaP) is the most common cancer and second most common cause of cancer-related deaths of men in the United Kingdom, with 10 164 deaths in 2003(Cancer Research UK, 2006. The diagnosis of CaP and in particular, the prediction of biopotential in individual patients can be very problematic.…”
mentioning
confidence: 99%